From Palladium Chalcogenides to Iron Complexes: Understanding Structure-Function Relationships in Crystals and in Molecules - Murray, G.M. (2021)
This thesis is an investigation into the structure-function relationship of a range of different materials and molecules. In Chapter 2 a newly synthesised hybrid material palladium sulfide nanoparticles encapsulated at milled carbon nanofibers (PdSx@CNFm). PdSx@CNFm is investigated for its activity towards the hydrogen evolution reaction (HER) and exhibits switchable behaviour even after extended chronoamperometric and cycling studies. Electrochemical performance is related to structure through high-resolution transmission electron microscopy (HRTEM) and electron dispersive X-ray spectroscopy (EDS) before and after activation. Changes of the internal corrugated structure of the carbon nanofiber support as well as changes to the PdSx nanoparticles are proposed as a mechanism for the switchable behaviour. Chapter 3 investigates a set of m-terphenyl iodide precursors based on 2,6-Ar2C6H3I where Ar = 2,4,6-Me3C6H2- (Mes) functionalised at the para position of the central aryl ring. Synthetic routes are described and carried out with the aim of studying the structural influence on the catalytic or magnetic properties of subsequent low-coordinate complexes. The concept is tested using a phenyl group initially followed by a pyrene moiety to exploit the non-covalent interactions between pyrene and carbon surfaces. Chapter 4 investigates a range of spin crossover (SCO) materials with large and flexible high charge tetracarboxylate anions (TCA) in the form [Fe(3-Bpp)2]2[TCA].xH2O (3-Bpp = 2,6-bis(pyrazol-3-yl)pyridine). Switchable magnetic bistability is investigated through magnetic measurements and correlated to X-ray crystallographic data to rationalise the deviation from expected magnetic behaviours.